Research trend on technology applications in social funding activities: A bibliometric analysis - Nurul Aien, Abd Aziz; Noraina Mazuin, Sapuan; Puteri Fadzline, Muhamad Tamyez; Suhal, Kusairi (Akademi Baru, 2026)
This study presents a bibliometric analysis of the evolving landscape of technology applications in social funding activities. It examined the interconnection of worldwide research activities using data obtained using VOSviewer software, which emphasizes the important role of technology in promoting social financing projects. The study was based on a network of bibliographic couplings with nodes indicating countries contributing to the subject and edges and the degree of research linkages between these countries. The results reflect a vibrant and dynamic research community with the United States, United Kingdom, China, and Canada emerging as important sites of innovation and cooperation. These nations have considerable bibliographic coupling, which suggests many related references and research interests. The network depicts the amount of research output and the complex patterns of international cooperation, with the United States being positioned as a prominent influencer owing to its wide connections and a central node in the network. The trend of technology applications in social financing is defined by various digital platforms, crowdfunding techniques, and financial technologies that redefine how social initiatives are financed and handled. The bibliometric map emphasizes the crucial role of technology in increasing the efficiency, reach, and effect of social financing across sectors and countries. Finally, this study offers a detailed review of the present status and development in technology applications within social financing and insights into the main actors and collaborative networks moving this sector ahead. It lays the groundwork for future research and development initiatives targeted at utilizing technology for social benefit.